Pembuatan Media Promosi Cetak Meliputi Spanduk, MMT, Kartu Nama Dan Brosur Di Perusahaan Kaos Semarang - Andik Prakasa Hadi; Ahmad Zainudin (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
Along with the development of increasingly modern times and increasingly sophisticated technology, many types of businesses are developing, one of which is a business in the convection field. The promotional media that is currently running at the Nanang Kaos company currently uses print media, only in the form of a nameplate in front of the shop, but the promotion system using a nameplate is also less effective, because the existence of the Nanang Kaos company itself is in the village area and has never carried out promotional activities for attracting new consumers, this makes it difficult for the Nanang Kaos Company to develop and is not well known by the wider consumer. So the author will add promotional media for the company, by adding print promotion media in the form of MMT Banners, Business Cards, and Brochures, it is hoped that consumers will know more about the products or services offered and know the existence of the company, which is a company engaged in convection.